PROJECT-BASED LEARNING (PJBL) DALAM PEMBELAJARAN PAI PELUANG, TANTANGAN, DAN DAMPAKNYA BERDASARKAN SISTEMATIC LITERATURE REVIEW - Widadi, Ahmad Setyo; Husniyatus Salamah Zainiyati; Hanun Asrohah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This study aims to analyze the implementation of Project-Based Learning (PjBL) in Islamic Education (PAI) through a Systematic Literature Review (SLR) approach. PjBL is an innovative student-centered learning method that integrates theory and practice to enhance cognitive understanding, psychomotor skills, and the strengthening of Islamic character. The analysis was conducted on various leading educational journals from 2020 to 2024 to identify the benefits, challenges, and impacts of PjBL implementation in the context of PAI. The findings reveal that PjBL effectively improves students' learning outcomes, including material comprehension, creativity, and social skills. This method also successfully fosters students' Islamic character, such as responsibility, empathy, and collaboration. PjBL aligns with the Merdeka Curriculum approach, which promotes active and collaborative learning. However, its implementation faces several challenges, including limited time, inadequate facilities, diverse student abilities, and a lack of teacher training. The implications of this study include the need to enhance teachers' competencies through continuous training, provide adequate facilities, and adjust the curriculum to optimally support PjBL implementation. This study highlights that PjBL is a potential approach to developing relevant, innovative, and meaningful PAI learning, capable of building a young generation that is knowledgeable, possesses strong Islamic character, and is prepared to face global challenges. Keywords: Islamic Education; Merdeka Curriculum; Project-Based Learning; Systematic Literature Review.